Polyphenols quantification by HPLC in propolis encapsulated in different matrices - Irigoiti, Yanet (2024)
One of the key components of propolis is polyphenols, a diverse group of naturally occurring compounds known for their biological properties. Polyphenols in propolis include flavonoids, phenolic acids, and their esters which are known for their anti-inflammatory, antimicrobial, and antiviral activities. Its antimicrobial properties are mainly due to the presence of flavonoids such as pinocembrin, galangin, and caffeic acid phenethyl ester. However, in their natural state, these compounds from propolis may have limited solubility in water, which can hinder their absorption in the body. Thus, encapsulation using various matrices may enhance their biodisponibility, making them more easily absorbed and utilized by the body. This study aimed to evaluate the polyphenol content, using HPLC, of propolis in different formulations: 10% w/v ethanolic extract (control) (PEE) and encapsulated in four different matrices: sodium alginate (CAP), co-crystallized with sucrose (CC), and freeze-dried without (FD) or with maltodextrin and whey protein (FDMWP). The encapsulated formulations were all in the form of dry powders which were properly dissolved, filtered, and diluted before analysis. The determination was carried out using an HPLC system coupled to a UV-Vis diode array detector (290 nm). For separating the compounds, a C18 column at 30°C and a gradient of methanol and acetic acid (1% w/v) (1mL/min) were used as eluents. The identification of individual compounds was performed by comparing the retention times and UV spectra with those of available standards stored in the library. Quantification was performed by integrating the chromatographic peaks and substituting the area values into the calibration curve made for each compound. The following compounds were reported: caffeic, cumaric, and ferulic acids, pinobanksin, apigenin, pinocembrin, crisin, and galangin. All of these compounds were found in PEE and FD. Pinocembrin, crisin and galangin were not detected in FDMWP, CC, and CAP. Considering the sum of the compounds, the lowest (0.75mg/g) and the highest (61.3 mg/g) concentrations were obtained for the samples FDMWP and FD, respectively. The results suggest that the freeze-drying technique, without the use of additives, was the best option to preserve the polyphenols of propolis.